Anastas, or the Origin of the Constitution, of J. Benet. Scenics Reflections About the Power (Castilla. Estudios de Literatura, 2012)
Anastas, or the Origin of the Constitution is a short play that thinks about the drama of the power, and its disastrous effects both on the one that holds it and on the crowd of people that suffer it. The analysis of the dramatic categories of the piece (the fable, the main characters, the space and the times) discovers to us a literary construction based on the radicalism of its confrontations and on the semiotic convergence of the plot disposition: the clash between the characters is always binary; the disposition of the reasons is a tragic strip that repeats itself one vignette after the other. The non-verbal signs of the scene reinforce this disposition, and everything in the drama helps to create an unbearable tension.